Manager characteristics and credit derivative use by US corporate bond funds - Dominika Paula Gałkiewicz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2014)
This study provides a comprehensive overview of the use of credit default swaps by U.S. corporate bond funds and analyzes in detail whether certain characteristics of managers, in addition to the fundamentals of a fund, determine how their use these credit derivatives. Results suggest that a manager's education, age, experience, and skill are positively correlated with a fund's CDS holdings. In particular, managers holding a master's degree or educated at prestigious universities prefer using CDS. However, funds with older, more experienced managers or these keeping higher assets under their management are more likely to take on credit risk via selling CDS protection. Younger managers or managers that were educated at prestigious universities rather tend to buy CDS protection possibly due to differing concerns about their careers. If considering the Heckman correction for self-selection of funds into CDS use, the aforementioned findings remain stable.
Keywords: G23; G28; 330; manager; manager characteristic; mutual fund; derivative use; credit default swap